Korelasi Antara Konsentrasi Oksigen Terlarut pada Kepadatan yang Berbeda dengan Skoring Warna Daphnia spp. [Correlation Between Dissolved Oxygen Concentration in Different Densities with Color Scoring Of Daphnia spp.] - A. Shofy Mubarak; Diah Ayu Satyari U; Rahayu Kusdarwati (Jurnal Ilmiah Perikanan dan Kelautan, 2010)
Abstract Dissolved oxygen is the parameters key of water quality. Low level of dissolved oxygen can affect the function and slow growth, can even cause death to fish in hypoxia condition. The aims of this experiment were to determine the effect of population density of Daphnia spp. of dissolved oxygen concentration and the correlation between dissolved oxygen concentration with color scoring of Daphnia spp. This method was experimental with Completely Randomized Design as experiment design with 6 treatments and 4 replications. The treatment that was given were the differences of Daphnia spp. density that consisted of treatment A (50 individu/200 ml), treatment B (250 individu/200 ml), treatment C (450 individu/200 ml), treatment D (650 individu/200 ml), treatment E (850 individu/200 ml), and treatment F (1050 individu/200 ml). The results showed that the difference of Daphnia spp. density showed highly significant effect of dissolved oxygen concentration of treatment medium (p<0,01). In addition, this experiment also showed that the dissolved oxygen concentration in treatment medium showed negative correlation with color score of Daphnia spp.